TBX20 promotes doxorubicin resistance in breast cancer cells through enhanced ABCC1 expression and inhibition of mitophagy - Shuai Nie; Dejian Liu; Jun Hu; Yu Gan; Liangliang Mi (PLoS ONE, 2026)
This study aimed to investigate the role and mechanism of T-box transcription factor 20 (TBX20) in doxorubicin resistance in breast cancer cells. RNA-seq data from breast cancer samples in the TCGA database were analyzed. Lentiviral vectors were used to establish TBX20 overexpression and silencing models in MCF-7 and MDA-MB-231 cells. Gene and protein expression were detected by qPCR and Western blot, respectively. Cell viability and the half-maximal inhibitory concentration of doxorubicin were measured using the CCK-8 assay. Apoptosis, migration, and invasion were analyzed by flow cytometry, wound healing assay, and Transwell assay. Mitophagy levels were assessed via immunofluorescence staining and western blotting. ChIP and dual-luciferase reporter assays were performed to validate the transcriptional regulation of ABCC1 by TBX20. Results showed that TCGA data analysis revealed a high expression of TBX20 in breast cancer tissues, which was positively correlated with ABCC1 expression. In MCF-7 and MDA-MB-231 cells, TBX20 overexpression significantly enhanced cell proliferation, migration, invasion, and resistance to doxorubicin, while suppressing the expression of mitophagy-related proteins LC3-II/LC3-I, PINK1, and BNIP3. ChIP and dual-luciferase reporter assays confirmed that TBX20 directly binds to and activates the ABCC1 promoter. Silencing of ABCC1 or restoration of mitophagy by CCCP reversed TBX20 overexpression‑induced doxorubicin resistance. TBX20 enhances the resistance of breast cancer cells to doxorubicin by transcriptionally upregulating ABCC1 and is correlated with the suppression of mitophagy.